Hierarchical porous ceramic material based on porous powder and preparation method

By using porous inorganic powder to prepare slurry and perform blanking, demolding and sintering treatment, the problems of cracking and energy consumption waste in the preparation of porous ceramics are solved, and the effects of resource reuse and cost reduction are achieved.

CN119528547APending Publication Date: 2025-02-28PIPECHINA SOUTH CHINA CO +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411521377.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

In the existing porous ceramic preparation methods, removing pore-forming agents may cause ceramic cracking, and porous materials are easily damaged during the preparation process, resulting in waste of energy consumption.

Method used

The slurry is prepared by porous inorganic powder, and the graded porous ceramic material is obtained by blanking, demolding and sintering. This method uses solid waste such as fly ash beads and perlite as raw materials to retain its pore structure and avoid additional introduction of pore structures.

Benefits of technology

The preparation of porous ceramics without destroying the porous structure of porous materials is achieved, the preparation process is simplified, the production cost is reduced, and the resource reuse is achieved, and the effect of environmental protection, resource saving and cost saving is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528547A_ABST
    Figure CN119528547A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of porous ceramics, in particular to a graded porous ceramic material based on porous powder and a preparation method. The method comprises the following steps: preparing slurry from porous inorganic powder, and sequentially carrying out blank making, demolding and sintering treatment on the slurry to obtain the graded porous ceramic material, wherein the porous inorganic powder comprises fly ash floating beads and perlite. According to the method, the solid waste with the porous inorganic powder is used as the raw material, the pore structure of the solid waste can be effectively utilized, and the pore structure does not need to be additionally introduced; resource recycling is achieved, and the effects of protecting the environment and saving resources and cost are achieved; in the sintering process, the structural collapse of the ceramic is avoided by controlling the temperature and the time, and finally the graded porous ceramic which is complete in structure and relatively uniform in floating bead distribution is obtained; the graded porous ceramic material has the advantages of uniform pore structure and high strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of porous ceramics, and in particular to a porous powder-based graded porous ceramic material and a preparation method thereof. Background Art

[0002] Porous ceramics have important applications in the fields of filtration and adsorption due to their high porosity, low density, corrosion resistance and high temperature resistance. In particular, graded porous ceramics play an extremely important role in the field of filtration catalysis. Usually, the raw materials for preparing porous ceramics are various solid high-density raw materials or liquid raw materials. Porous ceramics can be made by combining the above raw materials with main processing methods such as direct foaming method, sacrificial template method and replication method to introduce gas pores into the matrix in a direct or indirect way. Using homemade gelatin microspheres as sacrificial templates, Yan et al. adhered ceramic powders on the surface of gelatin microspheres by a granulation method, and obtained porous ceramic balls with a double-shell structure after sintering.

[0003] However, when porous ceramics are prepared by sacrificial template method or replication method, the removal of pore formers may cause problems such as ceramic cracking. Therefore, it is urgent to develop a simple and feasible method for preparing porous ceramics with porous structures.

[0004] Although porous ceramic powders contain micron and / or nanometer-scale pore structures, in actual applications, they usually need to be ball-milled for the preparation of ceramic materials, or molded under high pressure and then assisted by foaming or pore-forming methods to introduce pore structures into the matrix. These not only lead to the destruction of the pore structure of the raw materials, but also cause energy waste.

[0005] Therefore, using these porous materials to prepare porous ceramics without destroying their pore structure is beneficial to simplify the preparation process and reduce production costs. However, simply using the porous raw materials themselves as templates to prepare hierarchical porous ceramics remains a challenge. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a graded porous ceramic material based on porous powder and a preparation method thereof.

[0007] The technical solution of the present invention to solve the above technical problems is as follows:

[0008] The present invention provides a method for preparing a graded porous ceramic material based on porous powders, wherein porous inorganic powders are used to prepare slurry, and the slurry is subjected to blanking, demolding and sintering in sequence to obtain the graded porous ceramic material; wherein the porous inorganic powders include fly ash beads and perlite.

[0009] Based on the above technical solution, the present invention can also be improved as follows.

[0010] Furthermore, the mesh size of the perlite is 100-400 meshes.

[0011] Furthermore, the mass ratio of the fly ash beads to the perlite is 30-40:1.

[0012] Furthermore, the porous inorganic powder also includes diatomaceous earth, and the mass ratio of the diatomaceous earth to the perlite is 20-30:1.

[0013] Further, the method comprises the following steps:

[0014] S1, mixing the porous inorganic powder and the sol and stirring to obtain the slurry;

[0015] S2, adding monomers, crosslinking agents, dispersants, catalysts and initiators to the slurry in sequence and mixing them evenly, and preparing a green body from the mixed slurry using a mold;

[0016] S3, drying, and demoulding the green body;

[0017] S4, sintering the demoulding green body.

[0018] Furthermore, the dispersant includes one or more of polyethylene glycol, polyvinyl alcohol, and sodium carboxymethyl cellulose; the mass of the dispersant is 1%-3% of the porous inorganic powder.

[0019] Furthermore, the monomer is one or more of acrylamide, methacrylamide, and N-vinyl pyrrolidone; the mass of the monomer is 3wt.%-10wt.% of the porous inorganic powder.

[0020] Furthermore, the cross-linking agent is N,N'-methylenebisacrylamide and / or N-hydroxymethylacrylamide; the mass of the cross-linking agent is 1%-5% of the porous inorganic powder.

[0021] Furthermore, the catalyst is tetramethylethylenediamine and / or N,N-dimethylaniline; the mass of the catalyst is 0.5%-3% of the porous inorganic powder.

[0022] Furthermore, the initiator is ammonium persulfate and / or potassium persulfate, and the mass of the initiator is 0.5%-2% of the porous inorganic powder.

[0023] Furthermore, in step S3, the drying temperature is 50-100° C., and the drying time is 24-72 hours.

[0024] Furthermore, in step S4, the sintering temperature is 1000-1400° C., and the sintering holding time is 1-3 hours.

[0025] The present invention also provides a graded porous ceramic material based on porous powder, which is prepared by the above method.

[0026] Furthermore, the porosity of the graded porous ceramic material is 29.71%-71.28%, the water absorption is 24.63%-83.27%, and the compressive strength is 15.62-32.38 MPa.

[0027] The beneficial effects of the present invention are:

[0028] (1) The method for preparing a porous powder-based hierarchical porous ceramic material of the present invention uses solid waste (such as fly ash beads) with porous inorganic powder as raw materials, and can effectively utilize its own pore structure without the need to introduce additional pore structure;

[0029] (2) The porous powder-based hierarchical porous ceramic material preparation method of the present invention uses solid waste with porous inorganic powder (such as fly ash beads) as raw materials, which can achieve resource recycling and play a role in environmental protection, resource saving and cost saving;

[0030] (3) The method for preparing a graded porous ceramic material based on porous powder of the present invention, during the sintering process, the structural collapse of the ceramic is avoided by controlling the temperature and time, and finally a graded porous ceramic with a complete structure and relatively uniform distribution of floating beads is obtained;

[0031] (4) The graded porous ceramic material based on porous powder of the present invention has the advantages of uniform pore structure and high strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is an external morphology diagram of the graded porous ceramic obtained in Example 1 in the method for preparing a graded porous ceramic material based on porous powder of the present invention;

[0033] Figure 2 This is a scanning electron microscope image of the interior of the graded porous ceramic obtained in Example 1 in the method for preparing a graded porous ceramic material based on porous powder of the present invention;

[0034] Figure 3 This is an external morphology diagram of the graded porous ceramic obtained in Comparative Example 1 in the method for preparing a graded porous ceramic material based on porous powder of the present invention. DETAILED DESCRIPTION

[0035] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0036] The method for preparing graded porous ceramic materials based on porous powders of the present invention adopts porous inorganic powders to prepare slurry, and the slurry is subjected to blanking, demolding and sintering in sequence to obtain the graded porous ceramic material; wherein the porous inorganic powders include fly ash beads and perlite.

[0037] The method for preparing a graded porous ceramic material based on porous powder of the present invention uses solid waste (such as fly ash beads) with porous inorganic powder as raw materials, so that the prepared graded porous ceramic has the advantages of uniform pore structure and high strength. During the preparation process, the hollow structure of fly ash can be retained, thereby reducing the density of the porous ceramic. In addition, inorganic porous powders such as solid waste represented by fly ash beads are used as the main raw materials, which has a wide source of materials, low cost, and realizes the utilization of solid waste such as fly ash.

[0038] Preferably, the mass ratio of fly ash beads and perlite is 30-40:1; when the mass ratio of fly ash beads and perlite is too high, the strength of the prepared graded porous ceramic material will be reduced due to the high sintering temperature of the fly ash beads; and when the mass ratio is too low, too much perlite needs to be added, resulting in the formation of too much liquid phase during the sintering process and increasing the density of the graded porous ceramic material.

[0039] Preferably, the perlite is prepared into perlite powder by dry ball milling, and the ball-to-material mass ratio of the dry ball milling is 3:1.

[0040] Preferably, the perlite is specifically perlite powder, and its mesh number is 100-400 meshes; if the mesh number of the perlite powder is too high and the particle size is small, the perlite powder will be easy to agglomerate, which may cause uneven structure of the green body; if the mesh number of the perlite powder is too low and the particle size is large, due to the high-temperature expansion of the perlite powder, the volume is too large at the same mass, which will cause the green body to crack after firing, affecting the integrity of the graded porous ceramic material.

[0041] Preferably, the porous inorganic powder also includes diatomaceous earth, and the mass ratio of diatomaceous earth to perlite is 20-30:1. Diatomaceous earth is used as one of the raw materials because it also has the characteristics of being light and porous, and is also an ideal choice for preparing graded porous ceramics.

[0042] Preferably, the method for preparing a hierarchical porous ceramic material based on porous powder of the present invention comprises the following steps:

[0043] S1. Mixing and stirring the porous inorganic powder and the sol to obtain a slurry.

[0044] Preferably, the stirring time is controlled to be 10-30 min, and excessive rolling should be avoided during the stirring process to avoid breaking the fly ash beads and affecting the water absorption rate of the graded porous ceramic material.

[0045] Preferably, the sol is silica sol; the mass ratio of silica sol to fly ash floating beads is 3.5-4:1.

[0046] S2, add monomer, crosslinking agent, dispersant, catalyst and initiator to the slurry in sequence and mix them evenly, and use a mold to prepare the mixed slurry into a green body. After injection into the mold, quickly shake to remove the air inside the green body, and let it stand at room temperature.

[0047] Preferably, in the above process, each time an ingredient is added, it is stirred evenly before adding the next ingredient.

[0048] Preferably, the dispersant includes one or more of polyethylene glycol, polyvinyl alcohol, and sodium carboxymethyl cellulose; the mass of the dispersant is 1%-3% of the porous inorganic powder; the addition of the dispersant is beneficial to improving the uniformity of the raw material distribution, and can further improve the strength of the obtained graded porous ceramic material.

[0049] It should be noted that the mass percentages of other added ingredients such as dispersants are all measured based on the mass of the porous inorganic powder as 100%. The porous inorganic powder here, when containing only fly ash beads and perlite, is the sum of the masses of the two, and when containing diatomaceous earth, is the sum of the masses of the three.

[0050] Preferably, the monomer is one or more of acrylamide, methacrylamide, and N-vinyl pyrrolidone; the mass of the monomer is 3wt.%-10wt.% of the porous inorganic powder; excessive monomer usage will lead to increased cost of the graded porous ceramic material and difficulty in demolding, while too little monomer usage will lead to decreased quality and strength of the graded porous ceramic material, and may cause problems such as deformation or cracking.

[0051] Preferably, the crosslinking agent is N,N'-methylenebisacrylamide and / or N-hydroxymethylacrylamide; the mass of the crosslinking agent is 1%-5% of the porous inorganic powder; excessive use of the crosslinking agent will lead to an excessively high degree of crosslinking, thereby increasing production costs and causing difficulties in subsequent debonding; too little use may cause the polymer to be not tightly bonded, thereby reducing the strength of the graded porous ceramic material.

[0052] Preferably, the catalyst is tetramethylethylenediamine and / or N,N-dimethylaniline; the mass of the catalyst is 0.5%-3% of the porous inorganic powder; too much catalyst will form excess reaction intermediates, leading to undesirable side reactions and increasing the preparation cost; too little catalyst may limit the contact opportunities between the reactant molecules and the catalyst, thereby reducing the reaction rate.

[0053] Preferably, the initiator is ammonium persulfate and / or potassium persulfate, and the mass of the initiator is 0.5%-2% of the porous inorganic powder; too much initiator will lead to too fast or uncontrolled reaction, reducing the quality of the graded porous ceramic material; too little initiator will lead to a slower reaction rate, and it may take longer to reach the expected degree of reaction.

[0054] S3, drying, demoulding the green body. Specifically, the green body is placed in an oven for drying.

[0055] Preferably, in step S3, the drying temperature is 50-100° C., and the drying time is 24-72 hours.

[0056] S4, sintering the demoulded green body.

[0057] Preferably, the sintering temperature is 1000-1400°C, and the sintering holding time is 1-3h; if the sintering temperature is too high, part of the fly ash beads will begin to melt, the internal pore structure will collapse, and the porosity of the graded porous ceramic material will drop sharply; if the sintering temperature is too low, the graded porous ceramic material will not be sintered, resulting in its mechanical properties being too low.

[0058] In the preparation method of the graded porous ceramic of the present invention, the temperature and time are controlled during the sintering process to avoid the collapse of the ceramic structure, and finally a graded porous ceramic material with a complete structure and relatively uniform distribution of floating beads (such as the graded porous ceramic material prepared in Example 1, Figure 2 The sintering temperature is relatively low, but the hierarchical porous ceramic material with excellent performance can still be prepared, which greatly reduces energy consumption.

[0059] The porous powder-based graded porous ceramic material of the present invention is prepared by the above-mentioned method.

[0060] The porosity of the graded porous ceramic material is 29.71%-71.28%, the water absorption rate is 24.63%-83.27%, and the compressive strength is 15.62-32.38MPa. The graded porous ceramic of the invention has high strength and low density, and the pore structure of the porous powder is well maintained during preparation. The prepared graded porous ceramic has good properties such as heat insulation.

[0061] The present invention is described in detail below through specific examples and comparative examples.

[0062] Example 1

[0063] This embodiment provides a method for preparing a graded porous ceramic, and the specific steps are as follows:

[0064] The main raw materials are fly ash beads of 40 mesh, diatomaceous earth and perlite powder in a mass ratio of 32:28:1, and the above ingredients are added into silica sol. The mass ratio of silica sol to fly ash beads is 3.5-4:1.

[0065] Then, according to the method of the present invention, 3wt.% sodium carboxymethyl cellulose is added as a dispersant and stirred evenly. Then 12% acrylamide is added and stirred for 5 minutes, and then 2% N,N'-methylenebisacrylamide is added as a crosslinking agent and stirred evenly at a uniform speed, and then 1.5% ammonium persulfate is added as an initiator, and the stirring speed is increased and stirred evenly within 3 minutes to ensure full dissolution. 1% tetramethylethylenediamine is added as a catalyst and continued to be mixed evenly to obtain a blank.

[0066] The blank was injected into the mold, shaken rapidly to remove the air inside the blank, left to stand at room temperature for 2 hours, and then placed in an oven for drying at 60°C for 60 hours.

[0067] After demoulding, the sintering furnace is used for sintering. The maximum sintering temperature is 1200°C, and the heat preservation time is 2h to obtain graded porous ceramics.

[0068] This embodiment has carried out multiple groups of parallel experiments. According to the test, the porosity of the graded porous ceramics of this embodiment is 59.66-64.53%, the water absorption rate is 77.76-81.25%, and the compressive strength is 15.62-19.38 MPa.

[0069] The hierarchical porous ceramic of this embodiment has an external morphology as shown in the figure Figure 1 As shown in the scanning electron microscope image Figure 2 shown.

[0070] Example 2

[0071] This embodiment provides a method for preparing a graded porous ceramic, and the specific steps are as follows:

[0072] The 100-mesh fly ash floating beads and perlite powder with a mass ratio of 1.3-1.5:1 are used as main raw materials, and the above ingredients are added into silica sol. The mass ratio of silica sol to fly ash floating beads is 3.5-4:1.

[0073] Then, according to the method of the present invention, 2.5wt.% of polyethylene glycol is added as a dispersant and stirred evenly. Then 10% of acrylamide is added and stirred for 10 minutes, and then 1.5% of N,N'-methylenebisacrylamide is added as a crosslinking agent. After stirring evenly, 2% of ammonium persulfate is added as an initiator, and the stirring speed is increased. The stirring is evenly stirred within 5 minutes to ensure full dissolution. 0.5% of tetramethylethylenediamine is added as a catalyst, and the mixture is mixed evenly to obtain a blank.

[0074] The blank was injected into the mold, shaken rapidly to remove the air inside the blank, left to stand at room temperature for 4 hours, and then placed in an oven for drying at a temperature of 50°C for 72 hours.

[0075] After demoulding, the sintering furnace is used for sintering. The maximum sintering temperature is 1250°C, and the heat preservation time is 2h to obtain graded porous ceramics.

[0076] This embodiment has carried out multiple groups of parallel experiments. According to the test, the porosity of the graded porous ceramics of this embodiment is 51.22-59.18%, the water absorption rate is 71.13-78.87%, and the compressive strength is 17.36-23.21 MPa.

[0077] Comparative Example 1

[0078] The difference between this comparative example and Example 1 is that the dispersant is changed to sodium polyacrylate and the sintering temperature is 1200°C.

[0079] This comparative example has carried out multiple parallel experiments. According to the test, the porosity of the graded porous ceramics in this comparative example is 61.25-67.16%, the water absorption rate is 79.17-82.64%, and the compressive strength is 12.92-17.15 MPa.

[0080] The sample morphology of this comparative example is as follows Figure 3 As shown. Figure 3 It can be seen that the cross-section color of the sample of this comparative example is uneven, and the white raw materials are diatomite and perlite, which have a segregation phenomenon on the cross-section, indicating that the dispersion effect of sodium polyacrylate on the powder is poor. Therefore, although the porosity and water absorption of this comparative example are similar to those of the sample of Example 1, its compressive strength is significantly lower than that of the sample of Example 1.

[0081] Comparative Example 2

[0082] The difference between this comparative example and Example 2 is that the sintering temperature is 900° C. and the holding time is 3 h.

[0083] This comparative example has carried out multiple parallel experiments. According to the test, the porosity of the graded porous ceramics in this comparative example is 58.72-63.35%, the water absorption rate is 81.17-83.13%, and the compressive strength is 12.26-16.49 MPa.

[0084] The relevant parameter comparison table of Example 1-2 and Comparative Example 1-2 is shown in Table 1 below:

[0085] Table 1 Data of Examples and Comparative Examples

[0086] Serial number Porosity (%) Water absorption (%) Compressive strength(MPa) Example 1 59.66~64.53 77.76~81.25 15.62~19.38 Example 2 51.22~59.18 71.13~78.87 17.36~23.21 Comparative Example 1 61.25~67.16 79.17~82.64 12.92~17.15 Comparative Example 2 58.72~63.35 81.17~83.13 12.26~16.49

[0087] It can be seen from Table 1 that for the same ceramic raw material formula, the dispersant and sintering temperature have a greater impact on its strength. Therefore, in the actual operation process, the process can be adjusted according to the properties of the required sample.

[0088] In the description of the present invention, it should be noted that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.

[0089] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0090] In the present invention, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Moreover, a first feature being "above", "above" or "above" a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being "below", "below" or "below" a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.

[0091] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0092] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0093] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a hierarchical porous ceramic material based on porous powder, characterized in that: The porous inorganic powder is used to prepare the slurry, and the slurry is processed by blanking, demoulding and sintering in sequence to obtain the graded porous ceramic material; wherein the porous inorganic powder includes fly ash beads and perlite.

2. The method for preparing a graded porous ceramic material based on porous powder according to claim 1, characterized in that: The mesh number of the perlite is 100-400 meshes.

3. The method for preparing a graded porous ceramic material based on porous powder according to claim 1, characterized in that: The mass ratio of the fly ash floating beads to the perlite is 30-40:

1.

4. The method for preparing a hierarchical porous ceramic material based on porous powder according to claim 1, characterized in that: The porous inorganic powder also includes diatomaceous earth, and the mass ratio of the diatomaceous earth to the perlite is 20-30:

1.

5. A method for preparing a graded porous ceramic material based on porous powder according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, mixing the porous inorganic powder and the sol and stirring to obtain the slurry; S2, adding monomers, crosslinking agents, dispersants, catalysts and initiators to the slurry in sequence and mixing them evenly, and preparing a green body from the mixed slurry using a mold; S3, drying, and demoulding the green body; S4, sintering the demoulding green body.

6. The method for preparing a graded porous ceramic material based on porous powder according to claim 5, characterized in that: The dispersant includes one or more of polyethylene glycol, polyvinyl alcohol, and sodium carboxymethyl cellulose; the mass of the dispersant is 1%-3% of the porous inorganic powder.

7. The method for preparing a graded porous ceramic material based on porous powder according to claim 5, characterized in that: The monomer is one or more of acrylamide, methacrylamide, and N-vinyl pyrrolidone; the mass of the monomer is 3wt.%-10wt.% of the porous inorganic powder.

8. The method for preparing a graded porous ceramic material based on porous powder according to claim 5, characterized in that: The cross-linking agent is N,N'-methylenebisacrylamide and / or N-hydroxymethylacrylamide; the mass of the cross-linking agent is 1%-5% of the mass of the porous inorganic powder.

9. The method for preparing a graded porous ceramic material based on porous powder according to claim 5, characterized in that: The catalyst is tetramethylethylenediamine and / or N,N-dimethylaniline; the mass of the catalyst is 0.5%-3% of the porous inorganic powder.

10. The method for preparing a graded porous ceramic material based on porous powder according to claim 5, characterized in that: The initiator is ammonium persulfate and / or potassium persulfate, and the mass of the initiator is 0.5%-2% of the porous inorganic powder.

11. The method for preparing a graded porous ceramic material based on porous powder according to claim 5, characterized in that: In step S3, the drying temperature is 50-100° C., and the drying time is 24-72 hours.

12. The method for preparing a graded porous ceramic material based on porous powder according to claim 5, characterized in that: In step S4, the sintering temperature is 1000-1400° C., and the sintering holding time is 1-3 hours.

13. A hierarchical porous ceramic material based on porous powder, characterized in that: The method is prepared according to any one of claims 1 to 12.

14. The hierarchical porous ceramic material based on porous powder according to claim 13, characterized in that: The porosity of the graded porous ceramic material is 29.71%-71.28%, the water absorption rate is 24.63%-83.27%, and the compressive strength is 15.62-32.38 MPa.